Colloidal quantum dots photovoltaics with low-dimensional carbon nanomaterials - Tazawa, Y (2018)
Colloidal quantum dot (CQD)-based photovoltaics are an emerging low-cost solar cell technology with power conversion efficiencies exceeding 14%, i.e., high enough to be interesting for commercialization. Well-controlled and understood charge carrier transport through the device stack is required to make the next step in efficiency improvements.